2013
DOI: 10.1371/journal.pone.0077701
|View full text |Cite
|
Sign up to set email alerts
|

Low-Bone-Mass Phenotype of Deficient Mice for the Cluster of Differentiation 36 (CD36)

Abstract: Bone tissue is continuously remodeled by bone cells and maintenance of its mass relies on the balance between the processes of resorption and formation. We have reported the expression of numerous scavenger receptors, namely scavenger receptor (SR) class B type I and II (SR-BI and SR-BII), and CD36, in bone-forming osteoblasts but their physiological roles in bone metabolism are still unknown. To unravel the role of CD36 in bone metabolism, we determined the bone phenotype of CD36 knockout (CD36KO) mice and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 43 publications
3
34
0
Order By: Relevance
“…C, D ). This dramatic increase in trabecular bone volume is in contrast to the modest bone volume phenotypes of TSP1‐receptor deficient mice (CD47, CD36, β3 integrin−/−) and is consistent with TSP1 binding to multiple receptors. TSP1−/− mice also had significantly increased cortical bone thickness at 8‐, 16‐, and 32‐weeks of age and increased total cortical area at 32 weeks (Supplementary Table 1), indicating a geometrically larger bone and increased periosteal expansion in TSP1−/− compared to WT mice.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…C, D ). This dramatic increase in trabecular bone volume is in contrast to the modest bone volume phenotypes of TSP1‐receptor deficient mice (CD47, CD36, β3 integrin−/−) and is consistent with TSP1 binding to multiple receptors. TSP1−/− mice also had significantly increased cortical bone thickness at 8‐, 16‐, and 32‐weeks of age and increased total cortical area at 32 weeks (Supplementary Table 1), indicating a geometrically larger bone and increased periosteal expansion in TSP1−/− compared to WT mice.…”
Section: Resultssupporting
confidence: 64%
“…TSP1 is expressed by OBs and is present in osteoid and mineralized bone matrix, where it is directly deposited by bone‐forming OBs . TSP1 is involved in OB differentiation in part through activation of latent TGF‐β, and TSP1 receptors CD47 and CD36 also regulate OB . TSP1 is a regulator of NO in endothelial cells, platelets, and vascular smooth muscle cells, but only receptors CD36 and CD47 have been implicated in NO regulation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice deficient in the scavenger receptor type A locus show increased bone mass, increased femur length and decreased osteoclasts (30, 31). In contrast a low bone mass phenotype is seen in Cd36 −/− mice with diminished osteoblast differentiation (32). Thus, it is likely that defects in removal of apoptotic cells effects bone homeostasis but the roles of specific receptors remains to be established.…”
Section: Innate Immune Recognition Of Cell Death and Bonementioning
confidence: 99%
“…CD36 binding factors may stimulate bone resorption by osteoclasts [40]. CD36 knockout experiments in mouse model revealed that CD36KO mice tend to have low bone mass compare with wild type mouse [41]. ITGB1 is also a key gene in the leukocyte transendothelial migration pathway.…”
Section: Discussionmentioning
confidence: 99%